Application of a 3D hydrogel-based model to replace use of animals for passaging patient-derived xenografts - Sal Jones; Jennifer C. Ashworth; Marian Meakin; Pamela Collier; Catherine Probert; Alison A. Ritchie; Catherine L. R. Merry; Anna M. Grabowska (In vitro models, 2023)
Purpose This 3D in vitro cancer model for propagation of patient-derived cells, using a synthetic self-assembling peptide gel, allows the formation of a fully characterised, tailorable tumour microenvironment. Unlike many existing 3D cancer models, the peptide gel is inert, apart from molecules and motifs deliberately added or produced by cells within the model. Methods Breast cancer patient-derived xenografts (PDXs) were disaggregated and embedded in a peptide hydrogel. Growth was monitored by microscopic examination and at intervals, cells were extracted from the gels and passaged on into fresh gels. Passaged cells were assessed by qPCR and immunostaining techniques for the retention of characteristic markers. Results Breast cancer PDXs were shown to be capable of expansion over four or more passages in the peptide gel. Contaminating mouse cells were found to be rapidly removed by successive passages. The resulting human cells were shown to be compatible with a range of common assays useful for assessing survival, growth and maintenance of heterogeneity. Conclusions Based on these findings, the hydrogel has the potential to provide an effective and practical breast cancer model for the passage of PDXs which will have the added benefits of being relatively cheap, fully-defined and free from the use of animals or animal products. Encapsulated cells will require further validation to confirm the maintenance of cell heterogeneity, genotypes and phenotypes across passage, but with further development, including the addition of bespoke cell and matrix components of the tumour microenvironment, there is clear potential to model other cancer types.

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Pyrodiversity interacts with rainfall to increase bird and mammal richness in African savannas - Colin M. Beale; Colin J. Courtney Mustaphi; Thomas A. Morrison; Sally Archibald; T. Michael Anderson; Andrew P. Dobson; Jason E. Donaldson; Gareth P. Hempson; James Probert; Catherine L. Parr (Ecology Letters, 2018)
Fire is a fundamental process in savannas and is widely used for management. Pyrodiversity, variation in local fire characteristics, has been proposed as a driver of biodiversity although empirical evidence is equivocal. Using a new measure of pyrodiversity (Hempson et al .), we undertook the first continent‐wide assessment of how pyrodiversity affects biodiversity in protected areas across African savannas. The influence of pyrodiversity on bird and mammal species richness varied with rainfall: strongest support for a positive effect occurred in wet savannas (> 650 mm/year), where species richness increased by 27% for mammals and 40% for birds in the most pyrodiverse regions. Range‐restricted birds were most increased by pyrodiversity, suggesting the diversity of fire regimes increases the availability of rare niches. Our findings are significant because they explain the conflicting results found in previous studies of savannas. We argue that managing savanna landscapes to increase pyrodiversity is especially important in wet savannas.

A continental-scale study of seed lifespan in experimental storage examining seed, plant, and environmental traits associated with longevity - David J. Merritt; Amelia J. Martyn; Phillip Ainsley; Renee E. Young; Leahwyn U. Seed; Michael Thorpe; Fiona R. Hay; Lucy E. Commander; Nancy Shackelford; Catherine A. Offord; Kingsley W. Dixon; Robin J. Probert (Biodiversity and Conservation, 2014)